INFLUENCE OF MACROECONOMIC INDICATORS OVER QUALITY OF LIFE - Consuela DICU; Carmen SECARA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The main purpose of any human activity should be to ensure the highest possible quality of life, in full accordance with the personal ideals of each person. Quality of life is a concept that includes aspects associated with functionality and physical, mental, emotional, social health, personal perception, etc. Life satisfaction and well-being are more than the actual health of the body and the lack of disease, are a sum of aspects related to: physical health, mental health, emotional health, financial situation, occupation, education, social life, factors environmental. These factors are both objective and subjective and influence each other, the term quality of life being ultimately a cumulation of them.The article aims to describe the standard of living of the Romanian population in terms of quality of life. This will follow the evolution of macroeconomic indicators, at national and regional level, which highlight the standard of living between 1996 and 2020. The statistical data analyzed are taken from multiple sources: the database is Tempo-Online provided by the National Institute of Statistics, INS and EUROSTAT and are processed with Excel and Eviews software packages.